2005
DOI: 10.1159/000087804
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of EZH2, a Polycomb Group Protein, in Bladder Carcinoma

Abstract: Introduction: Recent experiments have demonstrated that polycomb group gene enhancer zeste homolog 2 (EZH2) is highly expressed in many cancer types. Therefore, we aim to demonstrate EZH2 gene expression in transitional cell bladder cancer. Patients and Methods: The reverse transcriptase-polymerase chain reaction (RT-PCR) was used for detection of EZH2 mRNA levels in healthy and cancerous human bladder specimens. Also, expression of the particular protein was determined by Western blotting and immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 31 publications
5
43
0
Order By: Relevance
“…In particular, high levels of EZH2 expression in gastric cancer tissues were significantly associated with the presence of metastasis indicating a possible role of this protein in gastric tumor spread. These results are in agreement with other reports indicating the re-expression of this protein in different human cancers (Varambally et al, 2002;Kleer et al, 2003;Dukers et al, 2004;Arisan et al, 2005;Gil et al, 2005;Weikert et al, 2005;Matsukawa et al, 2006), but pointing out that in the specific case of intestinal-type of gastric malignancy its re-expression occurs in tight correlation with the presence of metastasis, a factor that influence its prognosis. This study represents another evidence that the immunohistochemical investigation of various genes' expression could be of aid in understanding and predicting the aggressiveness of gastric malignancies.…”
Section: Kip1supporting
confidence: 93%
“…In particular, high levels of EZH2 expression in gastric cancer tissues were significantly associated with the presence of metastasis indicating a possible role of this protein in gastric tumor spread. These results are in agreement with other reports indicating the re-expression of this protein in different human cancers (Varambally et al, 2002;Kleer et al, 2003;Dukers et al, 2004;Arisan et al, 2005;Gil et al, 2005;Weikert et al, 2005;Matsukawa et al, 2006), but pointing out that in the specific case of intestinal-type of gastric malignancy its re-expression occurs in tight correlation with the presence of metastasis, a factor that influence its prognosis. This study represents another evidence that the immunohistochemical investigation of various genes' expression could be of aid in understanding and predicting the aggressiveness of gastric malignancies.…”
Section: Kip1supporting
confidence: 93%
“…In addition to these factors, many proliferative and prognostic markers, such as Ki-67, PCNA, p53, P-gp, Rb, EGFR, survivin, TERT, cyclin A, AKT, FAS, hMSH protein, CD100, cyclin D1, VEGF, Glut-1, ß-catenin, p-glycoprotein, HIF-1α, CD44, EGF-1R and ezrin, have been studied in recent years . EZH2, which is associated with malignancy in several cancers (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), might be a valuable marker of soft tissue sarcoma. Previous data have shown that EZH2 is specifically down-regulated in senescent fibroblasts, and that disruption of its expression retards cell proliferation and induces cell cycle arrest at the G2/M transition (44).…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 expression declines upon tissue maturation and differentiation, and is associated with malignancy in several cancers, including prostate, breast, bladder and gastric cancers, cutaneous melanoma and lymphoma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Almost all of these are epithelial malignant tumors or carcinomas, with the exception of lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in breast cancer, EZH2 expression is elevated in invasive carcinoma and metastases, and increased expression is strongly associated with a poor clinical outcome (25). Overexpression of EZH2 has also been described in other cancers including bladder (26)(27)(28), gastric (29), lung (30), and hepatocellular carcinoma (31). Deletions of microRNA-101, a negative regulator of EZH2 expression, have been described in prostate cancer, thus providing a mechanism for EZH2 overexpression (32).…”
Section: Ezh2 and Cancermentioning
confidence: 99%